RELEVANSI PEMIKIRAN ULAMA BUGIS DAN NILAI BUDAYA BUGIS (Kajian tentang ‘iddah dalam Tafsir Berbahasa Bugis Karya MUI Sulsel) - Yusuf, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2013)
This article temps to investigate Muslims Scholars of Bugis’ viewpoints base on the Qur’an in Tafesere Akorang Mabbasa Ogi by MUI of South Sulawesi when they ellaborated verses of the Quran on ‘iddah and its relevance to the value of local wisdom and culture of the Bugis. The coherence of their viewpoints and the values of local wisdom and culture of the Bugis has been ellaborated, they studied verses of the Quran about ‘iddah are relevant or related. The Bugis people have princpile and philosophy of life which are related to the doctrine of Islam. They can stand on the values of local culture, not only because of undertanding Islam well, but also because of their consistence to the philosophy of life. ‘Iddah which have arranged time limit s>squru>’ is not so difficult to be conducted by devorced women of Bugis. They are also able to protect themselves for not doing unproper thing (ihda>d), including proper marriageable. The devorced women have no problem and difficulty during the limitation of time (iddah and ihda>d) to not marry for the time being, and they can protect themselves because they hand the principle and values of siri’, lempu’, asitinajang, and paccing. These principles which become values of purity and self honor.